Correlation between Density and Resorption of Fresh-Frozen and Autogenous Bone Grafts. (24th June 2014) - Lumetti, Simone; Galli, Carlo; Manfredi, Edoardo; Consolo, Ugo; Marchetti, Claudio; Ghiacci, Giulia; Toffoli, Andrea; Bonanini, Mauro; Salgarelli, Attilio; Macaluso, Guido M.
Abstract : Trial Design . This analysis compared the outcome of fresh-frozen versus autologous bone block grafts for horizontal ridge augmentation in patients with Cawood and Howell class IV atrophies. Methods . Seventeen patients received autologous grafts and 21 patients received fresh-frozen bone grafts. Patients underwent CT scans 1 week and 6 months after surgery for graft volume and density analysis. Results . Two autologous and 3 fresh-frozen grafts failed. Autologous and fresh-frozen grafts lost, respectively, 28% and 46% of their initial volume ( P = 0.028 ) . It is noteworthy that less dense fresh-frozen blocks lost more volume than denser grafts (61% versus 16%). Conclusions . According to these 6-month results, only denser fresh-frozen bone graft may be an acceptable alternative to autologous bone for horizontal ridge augmentation. Further studies are needed to investigate its behaviour at longer time points.